2009
DOI: 10.1371/journal.pone.0004974
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of VEGFR2 and Not VEGFR1 Can Limit Diet-Induced Fat Tissue Expansion: Role of Local versus Bone Marrow-Derived Endothelial Cells

Abstract: BackgroundWe investigated if new vessel formation in fat involves the contribution of local tissue-derived endothelial cells (i.e., angiogenesis) or bone marrow-derived cells (BMDCs, i.e. vasculogenesis) and if antiangiogenic treatment by blockade of vascular endothelial growth factor (VEGF) receptors can prevent diet-induced obesity (DIO).Methodology/Principal FindingsWe performed restorative bone marrow transplantation into wild-type mice using transgenic mice expressing green fluorescent protein (GFP) const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…In brief, VEGF functions by binding two tyrosine kinase receptors, VEGF-R1 and VEGF-R2; the latter is expressed in vascular endothelial cells, and signaling through this receptor is critical for both physiological and pathological blood vessel formation. Blockade of VEGF-R2, but not VEGF-R1, restricts AT expansion and thus prevents the progression of DIO (81). Remarkably, blockade through use of a VEGF-R2 antibody can further inhibit preadipocyte differentiation (82).…”
Section: Angiogenesis a Rate-limiting Step For At Expansion And Remomentioning
confidence: 99%
“…In brief, VEGF functions by binding two tyrosine kinase receptors, VEGF-R1 and VEGF-R2; the latter is expressed in vascular endothelial cells, and signaling through this receptor is critical for both physiological and pathological blood vessel formation. Blockade of VEGF-R2, but not VEGF-R1, restricts AT expansion and thus prevents the progression of DIO (81). Remarkably, blockade through use of a VEGF-R2 antibody can further inhibit preadipocyte differentiation (82).…”
Section: Angiogenesis a Rate-limiting Step For At Expansion And Remomentioning
confidence: 99%
“…A recent study showed that blockade of VEGFR-2 but not VEGFR-1, using monoclonal antibodies, can limit diet-induced fat tissue expansion in mice. The results also indicated that angiogenesis from local preexisting vasculature, and not the contribution of bone marrow-derived cells, primarily sustains new vessel formation in fat tissue during diet-induced obesity (Tam et al, 2009). Another strategy to reduce fat mass via its vasculature may be to target prohibitin, a multifunctional membrane protein selectively expressed in adipose tissue endothelial cells (Kolonin et al, 2004).…”
Section: Pharmacologic Inhibition Of Angiogenesis Impairs Adipose Tismentioning
confidence: 99%
“…The similar distribution of white blood cells suggests that the rat antibody DC101 and the mouse antibody 1C8 did not elicit a markedly different immune response. In a previous study, treatment of C57Bl/6 mice with DC101 (40 mg/kg every 3 days) had no effect on body weight during the first 5-6 weeks of HFD feeding, but afterwards (weeks 6-13), the rate of weight gain decreased significantly compared with the HFD controls (Tam et al 2009). This was associated with a significantly decreased food intake in the DC101 group that was apparently not observed in the first 5-6 weeks.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study has revealed expression of different isoforms of VEGF-A, VEGF-B, and VEGF-C and the receptors VEGF-R1, VEGF-R2, and VEGF-R3 in subcutaneous (SC) and gonadal (GON) adipose tissues of mice (Voros et al 2005). Furthermore, blockade of VEGF-R2 but not VEGF-R1 in mice was shown to limit diet-induced fat tissue expansion and suggested a role in early phase fat tissue development (Tam et al 2009). In addition, several studies have suggested a link between the VEGF/VEGF-R2 pathway and insulin sensitivity and glucose tolerance (Elias et al 2012, Wada et al 2010.…”
Section: Introductionmentioning
confidence: 97%